Different Synchronization schemes for chaotic Rikitake systems - Khan, Mohammad Ali (Journal of Advanced Computer Science & Technology, 2012)
This paper presents the chaos synchronization by designing different type of controller. Firstly, we propose the synchronization of bi-directional coupled chaotic Rikitake systems via hybrid feedback control. Secondly we study the synchronization of unidirectionally coupled Rikitake systems using hybrid feedback control. Lastly, we investigate the synchronization of unidirectionally coupled Rikitake chaotic systems using tracking control. Comparing with all results finally we conclude that tracking control is more effective than feedback control. Simulation results are presented to show the efficiency of synchronization schemes.